Sorption energies estimation using Dubinin-Radushkevich and Temkin Adsorption isotherms for g-c3n4/fe3o4 composite - Taib, Nurul Izza; Saleh, Rozaina; Fisol, Aunie Aqelah; Ismail, Isma Iwana; Ismail, Nur Najieha (2024)
The discharge of dyes from various industrial activities has raised significant environmental concerns due to their persistence in the environment and potential to enter the food chain, posing threats to public health even at low concentrations. The textile industry significantly contributes to dye wastewater, representing approximately twothirds of the total dye waste generated on a global scale (Mittal et al., 2009; Ryu et al., 2023). Each year, approximately 300,000 tons of textile dyes are discharged into wastewater, leading to adverse effects on aquatic ecosystems and human health due to their toxic properties (Ogugbue & Sawidis, 2011; Zong et al., 2024). Methylene blue (MB), a widely used cationic dye, has been associated with various serious health issues such as increased heart rate, vomiting, shock, cyanosis, and jaundice, which are critical indicators of toxicity (Cai et al., 2020; Ilias et al., 2024). Moreover, methylene blue toxicity has implications beyond immediate health effects; chronic exposure can lead to tissue necrosis and hemolytic anemia (Xiang et al., 2019). The persistence of the dye in the environment and its ability to bioaccumulate in aquatic systems complicate the health risks associated with methylene blue. Effective removal strategies from wastewater are necessary to mitigate these dangers. The removal of heavy metals from wastewater is critical, and various conventional technologies such as chemical coagulation, precipitation, flocculation, membrane separation, and ion exchange have been employed. However, these methods often come with limitations, including high operational costs and generating secondary waste (Aragaw & Bogale, 2021; Hung et al., 2020). The adsorption method has attracted many researchers due to its simplicity, high efficiency, and cost-effectiveness, which is widely applied to most water treatment plants (Renu et al., 2017). The composite material g-C3N4/Fe3O4 has emerged as an effective adsorbent for the removal of dyes from aqueous solutions due to its unique structural and chemical properties. This composite has a high surface area and porosity, which facilitates the adsorption process. The interconnected porous networks in g-C3N4 composites enable rapid mass transfer of dye molecules, increasing its overall adsorption capacity (Pan et al., 2022). The incorporation of iron oxide (Fe3O4) in the composite further enhances its magnetic properties, facilitating the facile separation of the adsorbent from the solution after the adsorption process. This feature significantly enhances process efficiency and cost-effectiveness (Azali et al., 2023). The main objective of the study was to investigate the feasibility of using g-3N4/Fe3O4 as an adsorbent for the removal of MB at different initial concentrations and to assess the sorption energies using Dubinin-adushkevich and Temkin isotherms.